Peran Kyai Desa Pada Mediasi Perkara Perceraian Di Desa Kalisat Kecamatan Bungkal Kabupaten Ponorogo: indonesia - abidah markaban, zahrotul (Program Studi Hukum Tata Negara, 2025)
Islam recommends mutual efforts (ishlah) for peace when a dispute occurs, such as in the case of divorce, by bringing in an intermediary (hakam) or mediator when there is a dispute within the household. Mediation is not only carried out integrally in the Religious Courts, the Supreme Court can open the door to mediation outside the Religious Courts by optimizing the role of ulama and kyai who can act as mediators for parties who have civil disputes. The involvement of ulama and kyai as mediators is based on the opinion of interpretive ulama which requires that a peacemaker (mediator) has several requirements, including Khauf, Taqwa, Faqih and also understanding the issue being disputed. Kyai and ulama are figures who are seen as having these qualifications and charisma that can influence the conflicting parties. The existence of a kyai can be an intermediary to reconcile disputing parties in line with Islamic teachings, by reporting problems to the kyai. Apart from that, the hostility between both parties became less and less. This is better and lighter than the case going to court and being decided with a decision, because usually the defendant is defeated in the implementation of the decision which must be enforced by force. Keywords: Divorce, Kyai, Mediation